2004
DOI: 10.1038/sj.bjc.6601565
|View full text |Cite
|
Sign up to set email alerts
|

Filter cigarette smoking and lung cancer risk; a hospital-based case–control study in Japan

Abstract: Recent changes in the histology of lung cancer, namely a relative increase of adenocarcinoma compared to squamous cell carcinoma, might be due to a temporal shift from nonfilter to filter cigarettes. To investigate the association between type of cigarette and lung cancer by histological type, we conducted a case -control study in Japan, comprising 356 histologically confirmed lung cancer cases and 162 controls of male current smokers, who provided complete smoking histories. Overall, logistic regression analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
35
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 23 publications
3
35
2
Order By: Relevance
“…Our findings, like those of previous studies, showed that the relative risks for all types of lung cancer were significantly higher in current smokers than in never smokers. The relative risks we found, however, were lower than those reported in America and Europe (2,(15)(16)(17)21), but consistent with those reported in Japan and China (3,14,(18)(19)(20). Explanations proposed for our lower relative risks include fewer long-term heavy smokers, the smoking of cigarettes with lower amounts of tar and nicotine (28,29), later age of initiation, genetic differences such as CYP2A6 polymorphisms (3,30), and dietary and other nutritional factors.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Our findings, like those of previous studies, showed that the relative risks for all types of lung cancer were significantly higher in current smokers than in never smokers. The relative risks we found, however, were lower than those reported in America and Europe (2,(15)(16)(17)21), but consistent with those reported in Japan and China (3,14,(18)(19)(20). Explanations proposed for our lower relative risks include fewer long-term heavy smokers, the smoking of cigarettes with lower amounts of tar and nicotine (28,29), later age of initiation, genetic differences such as CYP2A6 polymorphisms (3,30), and dietary and other nutritional factors.…”
Section: Discussioncontrasting
confidence: 54%
“…Smoking is associated with all three types of lung cancer, but most studies suggest that the association with adenocarcinoma is weakest (1)(2)(3)(14)(15)(16)(17)(18)(19)(20)(21). Nearly all the data, however, come from case-control studies (1,2,14,(16)(17)(18)20), and prospective cohort studies generally include few nonsmokers who develop lung cancer (3,15,17,21). Furthermore, the studies focused on relative risk rather than absolute risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(34) Considering the higher probability of EGFR mutation in the Japanese population, one may assume that the overall incidence of EGFR mut NSCLC is also increasing. Although smoking-related factors such as the increased use of filtered tobacco are regarded as risk factors for adenocarcinoma, (35) those cases prevented by antismoking action may be EGFR wt NSCLC rather EGFR mut NSCLC. Therefore, identification of other potential risk factors for EGFR mut NSCLC as well as prevention strategies are required.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason is that epidemiological studies show no overall evidence of any increase in the risk of AdC associated with filter vs. plain or lower vs. higher tar cigarettes [5,[9][10][11][12]. Low tar filter cigarettes are associated with a small reduction in risk of SqCC, but not enough to explain the observed large rise over time in the frequency of AdC relative to SqCC.…”
mentioning
confidence: 91%